Analysis of Mn-deposits from the Alps - Karl Krainer; Helfried Mostler; Johann G Haditsch (PANGAEA, 1994)
Near Weissbach - Diessbach southeast of Lofer (Salzburg, Austria), at the western rim of the Steinernes Meer (Northern Calcareous Alps), the sedimentary sequence of a local Jurassic strike slip basin (pull apart basin) is exposed. This basin formed during the Hettangian (Lias) along E-W directed sinistral strike slip faults showing the structure of a halfgraben with a complex basin fill and asymmetric facies distribution. Along the scarp faults, some of which are still well exposed, different types of mass flows were deposited. In the more distal part red bedded liassic limestones with numerous turbidite and debris flow intercalations (Weissbach Formation) are developed. These slope sediments are overlain by large, up to several hundred meter thick synsedimentary Dachsteinkalk-blocks which slid into the basin and mark a phase of extreme high subsidence. The blocks are overlain by thin, grey and red liassic limestones with a hardground and manganese horizon on top. At places hardground and manganese horizon directly rest on top of the blocks and debris flows. The limestones of the slope facies contain a rich and interesting holothurian fauna, which differs significantly from that of the German Lias. Among the numerous holothurian sclerites there are some stratigraphically important and new species like Theelia liassica MOSTLER, Theelia multiundulata MOSTLER (Upper Hettangian-Lower Pliensbachian), Theelia loferensis MOSTLER (Pliensbachian) und Neomicroanlyx ingridae MOSTLER (Lower Toarcian). Laterally the slope facies interfingers with and is overlain by sediments of the Allgäu Formation, which also contains a manganese mineralization. Apart from the scarp faults the Liassic sequence is developed in a different facies: Dachsteinkalk is overlain by a thin sequence of red and grey, nodular cherty limestones, which upward grade into well bedded cherty limestones and into sediments of the Allgäu Formation. Within the sedimentary sequence of the basin manganese mineralisations occur in two different stratigraphic horizons: A manganese mineralization together with the hardground on top of the Dachsteinkalk-blocks and debris flows and overlying condensed limestones (Lower Toarcian), and a stratiform manganese mineralization within the Allgäu Formation (Aalenian-Bajocian). This stratiform mineralization should not be mixed up with manganese nodule mineralizations which are very common in the deep sea environment. Three different orefacies types have been recognized. Cu-, Ba- and SiO2 -content of the manganese ores and the occurring manganese ore sludges indicate a local source from hydrothermal solutions which ascended along a deep fault system.
Supplement to: Krainer, K et al. (1994): Jurassische Bekkenbildung in den Nördlichen Kalkalpen bei Lofer (Salzburg) unter besonderer Berücksichtigung der Manganerz-Genese = Manganese deposit genesis in the Jurrasic formations of the Northern Kalkalpen near Lofer (Salzburg). Abhandlungen der Geologischen Bundesanstalt, 50, 257-293, https://www.zobodat.at/pdf/AbhGeolBA_50_0257-0293.pdf